Fetal MRI Correlates with Postnatal CT Angiogram Assessment of Pulmonary Anatomy in Tetralogy of Fallot with Absent Pulmonary Valve. (22nd May 2013) - Sun, Heather Y.; Boe, Justin; Rubesova, Erika; Barth, Richard A.; Tacy, Theresa A.
Abstract In tetralogy of Fallot with absent pulmonary valve, pulmonary stenosis and regurgitation results in significant pulmonary artery dilatation. Branch pulmonary artery dilatation often compresses the tracheobronchial tree, causing fluid trapping in fetal life and air trapping and/or atelectasis after birth. Prenatal diagnosis predicts poor prognosis, which depends on the degree of respiratory insufficiency from airway compromise and lung parenchymal disease after birth. Fetal magnetic resonance imaging (MRI) has been useful in evaluating the effects of congenital lung lesions on lung development and indicating severity of pulmonary hypoplasia. This report is the first demonstrating the utility of fetal MRI in tetralogy of Fallot/absent pulmonary valve patients, which predicted postnatal pulmonary artery size and visualized airway compression and lung parenchymal lesions. The distribution of lobar fluid trapping on fetal MRI correlated with air trapping on postnatal computed tomography angiogram.